Komunitas Fitoplankton di Daerah Litoral Danau Maninjau dan Sungai Ranggeh, Kabupaten Agam Kaitannya dengan Kandungan Nutrien - Fachmijany Sulawesty; Yustiawati; Siti Aisyah, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Phytoplankton Community Relationship with Nutrient Content in the Littoral Areas of Lake Maninjau and Ranggeh River, Agam Regency. Phytoplankton in Lake Maninjau is a food source for fish and plankton-eating fish such as Bada fish (Rasbora sp.), Lake Maninjau endemic fish that have high economic value. Nutrients such as nitrogen and phosphorus would be the limiting factors for phytoplankton growth. This observation aims to determine the composition and abundance of phytoplankton to nutrient content in the littoral areas of Maninjau Lake and Ranggeh River. The observations were conducted on April, July, August, September, October, and November 2018 at several observation stations. The results show that there were phytoplankton groups, ie. Chlorophyta (53 species), Bacillariophyta (35 species), Cyanophyta (six species), Euglenophyta (five species), and Dinophyta (two species). The phytoplankton abundance in Maninjau littoral region ranged from 0.07 x 106 - 5.8 x 106individual.L-1, while in Ranggeh River ranges from 0.0016 x 106 - 2.1 x 106individual.L-1. In July 2018, the most abundant species was Microcystis aeruginosa (Cyanophyta), in August and September were Synedra ulna (Bacillaryophyta) while in October and November were Cylindrospermopsis raciborskii (Cyanophyta). Based on the diversity index, evenness index and dominance index, the phytoplankton community in the littoral area of Maninjau Lake was unstable compared to Ranggeh River. Principal component analysis showed that the abundance of Cyanophyta in the Maninjau littoral area was influenced by the concentration of phosphorus.